Pre-mix model for strategic block and sublevel caving production planning - O.'Connor, S.; Lolon, S.; Perez Strutz, C.; Wafforn, M.; Barich, C. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Block and sublevel caving (BC and SLC) are highly productive mass underground mining methods, but performance is strongly influenced by material flow, mixing and draw. Pre-mixing of ore and waste prior to extraction is critical for controlling dilution, recovery and draw efficiency. This paper presents a practical, deterministic pre-mix model for BC and SLC operations that integrates gravity-based vertical flow and spatial awareness of drawpoint locations to estimate extraction ratios and mixed grades. Amplify Mine Planning has implemented cave flow pre-mix formulas within Deswik Planning, streamlining the determination of step-outs and mixed grades. This simple approach enables rapid evaluation and strategic comparison of footprints and production plans for mass mining methods (e.g. BC and SLC), resulting in significant time and cost savings in the early study phase. By leveraging standard production and custom fields, the premix model is transparent and auditable, providing clear strategic value at the conceptual study level. A case study of Pan American Silver’s La Colorada Skarn project demonstrates the model’s application and validation. Results highlight the revealed opportunities to optimise footprint location and draw strategy, and to improve ore recovery while minimising waste inflow. The model has been peer-validated against an advanced cellular automata flow modelling tool, in which the estimated pre-mix grades agree within 1% of the counterpart flow model results. The strategic pre-mix model provides a fast, cost-effective and transparent approach for early-stage mine planning. Though the method will not replace the advanced cave flow and geotechnical assessment modelling, it enables rapid generation of production plan scenarios per mining method and footprint, and parametric and sensitivity analyses, supporting informed forecasts and decisions early in the study phase. By streamlining evaluation of the method, footprint and draw strategy, the model delivers actionable insights and economic benefits. This empowers planners to optimise BC and SLC planning and forecasting with greater confidence.